Hot-Dip Aluminizing of Low Carbon Steel Using Al-7Si-2Cu Alloy Baths. (18th September 2013) - Huilgol, Prashanth; Bhat, Suma; Bhat, K. Udaya
Abstract : Hot-dip aluminizing of low carbon steel was done in molten Al-7Si-2Cu bath at 690°C for dipping time ranging from 300 to 2400 seconds. Characterization of the intermetallics layer was done by using scanning electron microscope with energy dispersive spectroscopy. Four intermetallic phases, τ 5 -Al7 Fe2 Si, θ -FeAl3, η -Fe2 Al5, andτ 1 -Al2 Fe3 Si3, were identified in the reaction layer.τ 5 - Al7 Fe2 Si phase was observed adjacent to aluminum-silicon topcoat, θ -FeAl3 betweenτ 5 andη -Fe2 Al5, η -Fe2 Al5 adjacent to base material, andτ 1 -Al2 Fe3 Si3 precipitates within Fe2 Al5 layer. The average thickness of Fe2 Al5 layer increased linearly with square root of dipping time, while for the rest of the layers such relationship was not observed. The tongue-like morphology of Fe2 Al5 layer was more pronounced at higher dipping time. Overall intermetallic layer thickness was following parabolic relationship with dipping time.